Circulating serum preptin levels in women with polycystic ovary syndrome: A systematic review and meta-analysis - Seyed Sobhan Bahreiny; Elnaz Harooni; Mohammad Reza Dabbagh; Reza Ebrahimi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder with complex pathogenesis and metabolic complications, such as insulin resistance. Among the new markers, preptin seems to play a significant role in metabolic disorders. Objective: This meta-analysis was conducted to determine the relationship between circulating preptin levels and PCOS. Materials and Methods: A systematic review and meta-analysis was performed to identify relevant articles in electronic databases such as PubMed, Web of Science, Scopus, Cochrane, EMBASE, and the Google Scholar search engine, using a predefined search strategy. A random-effects model was used to combine standard mean difference (SMD) and 95% CI to compare results between groups. Meta-regression and subgroup analysis were also performed to reveal the sources of heterogeneity. Results: The meta-analysis encompassed a total of 8 studies and 582 participants. The results indicate a statistically significant association between PCOS and serum preptin levels, with a pooled standardized mean difference (SMD = 1.35; 95% CI]: 0.63-2.08; p < 0.001). Further analysis suggested a significant difference in serum preptin levels between women with PCOS and higher homeostatic model assessment for insulin resistance ratio (SMD = 2.40; 95% CI: 1.17-3.63; p < 0.001) within the subgroup. Conclusion: Our meta-analysis shows that increased serum preptin levels are associated with PCOS, suggesting that preptin may be related to the pathogenesis of PCOS and may be recognized as a novel diagnostic biomarker for PCOS. However, further studies are needed to confirm our results.